Slovene music in the later 20th and early 21st centuries - O'Loughlin, Niall (Muzikološki zbornik, 2009)
Music in Slovenia in the late 20th and early 21st centuries tends towards either modernism or postmodernism. However, with the constant sharing of techniques by a wide range of composers, this distinction is becoming increasingly irrelevant.
Keywords: glasba; modernizem; music; postmodernizem; Slovenia; Slovenija